Pengaruh Latihan Lateral Feet Drill The Tanggo Dan Five Court Terhadap Kelincahan Otot Tungkai Pada Klub Galaxy Fc. Bima - Marzuki, Ismail; Soemardiawan, Soemardiawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The research objective is the slow movement of the feet in changing the direction of running due to the lack of agility (agility) in the players due to the ineffective training undertaken, the training methods that are not good in terms of running, attacking, passing and dribbling football are done slowly and easily grab the ball. The sampling technique used purposive sampling. The researcher used the entire population to be used as research samples, namely all Galaxy FC clubs totaling 20 active people, where the sample was divided into two, namely 10 Lateral Feet Drill The Tanggo players and 10 Five Court players. The research design used